PENGARUH PENAMBAHAN ALKANOLAMIDA TERHADAP KARAKTERISTIK PEMATANGAN DAN KEKERASAN VULKANISAT KARET ALAM BERPENGISI KAOLIN - Indah M.S. Sitorus; Yudha Widyanata; Indra Surya (Jurnal Teknik Kimia USU, 2013)
By using a semi-efficient sulphur accelerated vulcanization system, an investigation of the effect of alkanolamide on cure characteristics and hardness properties of kaolin-filled natural rubber compounds was carried out. Alkanolamide was synthesized from Refined Bleached Deodorized Palm Stearin (RBDPS) and diethanolamine. Alkanolamide was incorporated into the kaolin filled-natural rubber compound at 1.0; 3.0; 5.0 and 7.0 Parts per-Hundred RubbeR (phr). It was found that alkanolamide gave shorter scorch time and cure time. Alkanolamide also exhibited higher torque different, crosslink density, and hardnessup to 5.0 phr and then decreased with further increasing the loading of alkanolamide.